2009
DOI: 10.1021/jf900433d
|View full text |Cite
|
Sign up to set email alerts
|

Cephalexin Residue Detection in Milk and Beef by ELISA and Colloidal Gold Based One-Step Strip Assay

Abstract: An evaluation of a rapid enzyme-linked immunosorbent assay (ELISA) and colloidal gold based one-step strip assay for cephalexin (CEX) residue detection in milk and beef is described. A monoclonal antibody (mAb) against CEX was produced using cephalexin-bovine serum albumin (CEX-BSA) conjugate as the immunogen, which exhibited no cross-reactivity with applied chemicals in the studied concentration range. The detection limit of rapid ELISA was calculated as 0.39 microg/kg in PBS and 19.5 microg/kg in beef and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 23 publications
1
19
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17] In recent years, immunological techniques have attracted increasing attention by those working in cultural heritage. For example, milk residues, 18,19 protein-bound materials and organic bones have been detected, [20][21][22][23][24][25] and all of these studies have demonstrated that immunoassays have the potential to identify and localize the proteins in archaeological materials both rapidly and effectively. However, most of the antibodies used in these immunoassays are readily commercially available "off-theshelf", and the need for tailored antibodies for targeted cultural heritages with high sensitivity and specificity is increasingly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] In recent years, immunological techniques have attracted increasing attention by those working in cultural heritage. For example, milk residues, 18,19 protein-bound materials and organic bones have been detected, [20][21][22][23][24][25] and all of these studies have demonstrated that immunoassays have the potential to identify and localize the proteins in archaeological materials both rapidly and effectively. However, most of the antibodies used in these immunoassays are readily commercially available "off-theshelf", and the need for tailored antibodies for targeted cultural heritages with high sensitivity and specificity is increasingly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody production Different approaches have been described to produce immunogenic cephalosporin conjugates, including the use of bifunctional coupling reagents such as glutaraldehyde [24,26,31], o-phthaldialdehyde [35] and carbodiimide [23,25,27,29] or heterobifunctional NHS-ester cross-linking reagents [36]. In most cases the cephalosporin-protein conjugation was performed at physiological or slightly acidic pH conditions to avoid cleavage of the beta-lactam ring.…”
Section: Resultsmentioning
confidence: 99%
“…3 A comparison of our results with previously published methods for cefquinome, ceftiofur/desfuroylceftiofur and cephalexin reveals that our mAb-based EIAs are at least similar or even better in sensitivity. Most data are available for cephalexin, and reported IC 50 values range from 0.6 to 6 ng mL −1 [24,26,29,37]. Based on mAbs against desfuroylceftiofur, Rose et al [30] established an EIA for the detection of ceftiofur, the IC 50 value was at 0.33 ng mL −1 .…”
Section: Characterization Of Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To help address these issues, there has been much research devoted to the development of immunochromatographic test strip technology (Weller, 2000). This technology has been utilised for detection of drug residues (Chen et al, 2009) and drugs of abuse by transferring the immunoassay process onto a single-use test strip that generates a colour response after the sample has flowed over the immobilised protein conjugate. Such tests however, are largely semi-quantitative and so can be of limited use when a concentration result is required rather than a simple yes/no answer.…”
Section: Introductionmentioning
confidence: 99%